2013
DOI: 10.1021/jp403006m
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics Simulation of the Dissociation of Ethanol on a Nickel Cluster: Understanding the Initial Stage of Metal-Catalyzed Growth of Carbon Nanotubes

Abstract: The dissociation of ethanol molecules on a nickel cluster was investigated by ab initio molecular dynamics and nudged-elastic-band (NEB) simulations to discuss the initial stage of metal-catalyzed growth of carbon nanotubes via alcohol catalytic chemical vapor deposition. Both C− C and C−O bonds in ethanol molecules are dissociated on the nickel cluster, which is followed by the formation of various reaction products such as hydrogen atoms and molecules, carbon monoxide, oxygen atoms, water, ethylene, methane,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 58 publications
3
35
0
1
Order By: Relevance
“…The inhibition of the dehydrogenation has been found in the case of ethanol molecules with the Ni cluster [30,31]. By removing the hydrogen atoms on the Ni cluster in the middle of the simulation, it has been confirmed that the adsorption and dehydrogenation of the ethanol molecules reoccurred.…”
Section: Introductionmentioning
confidence: 77%
“…The inhibition of the dehydrogenation has been found in the case of ethanol molecules with the Ni cluster [30,31]. By removing the hydrogen atoms on the Ni cluster in the middle of the simulation, it has been confirmed that the adsorption and dehydrogenation of the ethanol molecules reoccurred.…”
Section: Introductionmentioning
confidence: 77%
“…On the other hand, we have closely discussed the dissociation of carbon source molecules on various catalytic metals based on the ab initio MD simulation [29][30][31][32][33], which takes into account both the chemical reaction with the accuracy of the ab initio calculation and the dynamics of atoms simultaneously, in order to discuss the initial stage of the CNT growth. Up to now, we have revealed the bond dissociation mechanism of ethane [29] and ethylene [30] on a nickel (1 1 1) surface, that of ethanol [31,32] and ethylene [33] on a nickel cluster, and that of methane and derivative fragment molecules on a copper (1 1 1) surface [34].…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of reaction mechanisms over solid catalysts normally employs a combination of plane wave basis set, pseudopotentials and periodic conditions [5,6,12,22,23]. This approach has the advantage of allowing the reaction to take place over a relatively large surface in an attempt to reproduce the real experimental conditions.…”
Section: Validation Of the Cluster Calculationsmentioning
confidence: 99%
“…The formation of such byproducts is governed by the several reaction intermediaries and transition states, in such a way that a knowledge of how these species behave along the reaction path is crucial to understand and control their role. Additionally, decomposition of ethanol over metal catalysts is among the methods for the growth of carbon nanotubes [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation